Exploring the role of the NO‑detoxifying enzyme HmpA in the evolution of domesticated Alfalfa Rhizobia - Frare, Romina Alejandra; Pascuan, Cecilia Gabriela; Galindo Sotomonte, Luisa Fernanda; McCormick, Wayne; Soto, Gabriela Cynthia; Ayub, Nicolás Daniel (Springer, 2022)
We have previously shown the extensive loss of genes during the domestication of alfalfa rhizobia and the high nitrous oxide emission associated with the extreme genomic instability of commercial inoculants. In the present note, we describe the molecular mechanism involved in the evolution of alfalfa rhizobia. Genomic analysis showed that most of the gene losses in inoculants are due to large genomic deletions rather than to small deletions or point mutations, a fact consistent with recurrent DNA double-strand breaks (DSBs) at numerous locations throughout the microbial genome. Genetic analysis showed that the loss of the NO-detoxifying enzyme HmpA in inoculants results in growth inhibition and high DSB levels under nitrosative stress, and large genomic deletions in planta but not in the soil. Therefore, besides its known function in the effective establishment of the symbiosis, HmpA can play a critical role in the preservation of the genomic integrity of alfalfa rhizobia under host-derived nitrosative stress.